(untitled) (Jurnal Ilmu Komunikasi dan Bisnis, 2023)
Apart from being used to socialize, Instagram social media is also used as a medium for promotions, buying and selling transactions. The occurrence of various frauds in online transactions sets a precedent that can be detrimental to these online business actors. In online transactions, building trust is an important step that must be taken by business actors, especially for business actors who are just starting their business. @Ricellystore is a new online business actor engaged in the used gadget sector, but they are able to build trust in a relatively short time with sales figures increasing significantly every month. This study aims to find out how the digital marketing communication strategy carried out by @Ricellystore on Instagram builds customer trust. This study uses a descriptive qualitative approach, where data is obtained through interviews, observation, and documentation. The results of the research show that the @Ricellystore digital marketing communication strategy starts with strengthening Perceived web vendor reputation and Perceived web quality, making their store reachable and available, having added value, and maximizing unpaid promotion with the power of word of mouth (WOM) and resellers from their customers.